URGENSI INTEGRITAS GURU PAK DALAM MENJALANKAN TUGAS DAN TANGGUNG JAWAB DI SEKOLAH - febriyanti siramba (Sekolah Tinggi Teologi Mawar Saron Lampung, 2025)
An educational institution is a place where an educational process takes place. Schools are one part of educational institutions that take a role in achieving the success of educational goals. The role of teachers is one of the important components in achieving the goal of educational success with their duties and responsibilities in carrying out teaching, educating, and guiding student activities. Teachers have great duties and responsibilities. Therefore, it is very necessary for the integrity of teachers in teaching, educating, and guiding students. The purpose of this research is: to determine the urgency of the integrity of PAK teachers in carrying out their duties and responsibilities in schools. By using qualitative research methods of literature study. The conclusion is that the integrity of PAK teachers is needed in their duties and responsibilities in teaching, educating, and guiding students.